The silver ring : activity book (London : Ladybird Book, 2019)
Phonics: igh ear air ure Sight words: come from so stop we what Theme: Being patient Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language.
Keywords: English - language; English - language - problems